Activity Levels in Seven Cats with Osteoarthritis Monitored by GPS Tracker Following Frunevetmab Injection - Power, Ashley M.; St Germaine, Lindsay L. (VCOT Open, 2024)
Objective The goal of the current pilot study was to use a commercially available accelerometer (Tractive GPS Tracker for Cats) in a setting evaluating the activity level of cats exhibiting different forms of osteoarthritis in their natural habitat before and after treatment with frunevetmab, using each individual cat as its own control. We hypothesized that treatment with frunevetmab would be associated with increased activity level.Methods Activity data, measured as minutes of active time per day via accelerometer worn on a collar, were obtained from seven employee-owned cats with radiographically confirmed evidence of osteoarthritis. Cats were randomly assigned to two different protocols in which treatment and no treatment (control) were reversed; that is, undergoing the control period prior to treatment with frunevetmab (“standard” control) versus first assessed without treatment (control period) followed by frunevetmab treatment after minimum 30-day washout period (“inverse” control period).Results Activity time, on average, was 30 minutes longer per day for frunevetmab versus control (p = 0.007).Conclusions Based on measurements obtained with piloted use of the Tractive, the activity level in osteoarthritic cats appeared greater when treated with frunevetmab compared to self-control without frunevetmab treatment (either pretreatment or following washout period). The small sample size here does warrant caution in interpreting results for a broader population.
Keywords: arthritis; chronic pain; monoclonal antibody; frunevetmab; feline